Causes of Student Errors in Solving Numeration Problems : A Case Study on Students with a Strongly Field Independent Cognitive Style - Salman Alfarisi; Sukoriyanto Sukoriyanto; Abdur Rahman As’ari (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to uncover the causes of errors in solving numeracy problems related to trigonometry among students with a strongly field-independent cognitive style. The research method employs a case study with a qualitative approach. The subjects of this study are students of class XI MA Ibadurrochman Malang. The instrument in this study consists of the main instrument, namely the researcher himself and supporting instruments consisting of GEFT (Group Embedded Figure Test) sheets and Numeration Problem Solving Test Sheets (TPMN) and interview guidelines. This data analysis technique used interactive model analysis. The research findings indicate that the causes of student errors in solving numeracy problems are primarily rooted in their previous knowledge, which results in these errors. In other words, their previous knowledge is unable to serve as a foundational material for generating ideas in solving new problems encountered. These new problems related to trigonometry are used not only to apply previously acquired knowledge to the issues at hand but also to learn new mathematical concepts. Consequently, numeracy problems become a solution for students to study mathematics coherently.